2021
DOI: 10.1029/2021jd034995
|View full text |Cite
|
Sign up to set email alerts
|

Stratospheric Fluorine as a Tracer of Circulation Changes: Comparison Between Infrared Remote‐Sensing Observations and Simulations With Five Modern Reanalyses

Abstract: Using multidecadal time series of ground-based and satellite Fourier transform infrared measurements of inorganic fluorine (i.e., total fluorine resident in stratospheric fluorine reservoirs), we investigate stratospheric circulation changes over the past 20 years. The representation of these changes in five modern reanalyses is further analyzed through chemical-transport model (CTM) simulations. From the observations but also from all reanalyses, we show that the inorganic fluorine is accumulating less rapidl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 104 publications
6
6
0
Order By: Relevance
“…Those asymmetries are consistent with the results of Strahan et al (2020), who found significantly negative mean AoA trends in the SH compared to the NH using HCl and HNO 3 measured at several ground-based FTIR stations. In addition, the hemispheric differences of the N 2 O trends are also consistent with the results of Prignon et al (2021), who found larger and more significant F y trends from FTIR above Jungfraujoch than above Lauder.…”
Section: Stratospheric N 2 O Columns and Their Trendssupporting
confidence: 88%
See 4 more Smart Citations
“…Those asymmetries are consistent with the results of Strahan et al (2020), who found significantly negative mean AoA trends in the SH compared to the NH using HCl and HNO 3 measured at several ground-based FTIR stations. In addition, the hemispheric differences of the N 2 O trends are also consistent with the results of Prignon et al (2021), who found larger and more significant F y trends from FTIR above Jungfraujoch than above Lauder.…”
Section: Stratospheric N 2 O Columns and Their Trendssupporting
confidence: 88%
“…However, this application of the irregular sampling of ACE-FTS to the model output consistently enhances the N 2 O trends, both positive and negative. Using continuous time sampling on native model grids, ERAI, and ERA5 to a lesser extent, still simulate the meridional dipole in the N 2 O trends, consistently with a large number of modeling studies using both idealized and real tracers (e.g., Chabrillat et al, 2018;Ploeger & Garny, 2022;Prignon et al, 2021), but MERRA2, JRA55 and both WACCM versions fail to reproduce the meridional dipole. The inherently limited spatial and temporal sampling of ACE-FTS, and its effect on N 2 O trends, highlight the necessity to carry out the N 2 O trend analysis discussed here using a satellite instrument with a more regular coverage.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations